Path dependency and institutional change - Fernandes, Antonio Sérgio Araújo (Universidade Estadual Paulista / UNESP, 2014)
The purpose of this article is to bring to the fore the discussion of the historical-institutional studies about the concept of path dependence and its relation to institutional change. The importance of this discussion is the need to understand the motives that enter institutions in a context of constant change, even if you are trying to explain institutional stability.